Surgical Treatment of Intervertebral Disc Extrusion in Three Cats - BishalBhattarai; Nikolay AndreivichKozlov; TomášLipták; Sergey Pozyabin; NatáliaŠurín Hudáková; Natalya AnatolyevnaSlesarenko; Mária Kuricová (The Indian Veterinary Journal, 2024)
Intervertebral disc disease (IVDD) is a well-known cause of the spinal cord injury in dogs presented with neurological dysfunction. There is a lot of knowledge about IVDD in dogs, including breed and age predispositions, typical manifestations, and the response to therapy. In contrast, IVDD in cats occurs much less frequently, and there is a limited number of studies and lack of objective information. We describe the clinical presentation, diagnosis and surgical therapy of three client owned cats with intervertebral discs extrusions. No complications or recurrence were observed perioperatively and during 12-month-follow-up period.